2013
DOI: 10.1186/1755-8166-6-16
|View full text |Cite
|
Sign up to set email alerts
|

Array CGH as a first line diagnostic test in place of karyotyping for postnatal referrals - results from four years’ clinical application for over 8,700 patients

Abstract: BackgroundArray CGH is widely used in cytogenetics centres for postnatal constitutional genome analysis, and is now recommended as a first line test in place of G-banded chromosome analysis. At our centre, first line testing by oligonucleotide array CGH for all constitutional referrals for genome imbalance has been in place since June 2008, using a patient vs patient hybridisation strategy to minimise costs.FindingsOut of a total of 13,412 patients tested with array CGH, 8,794 (66%) had array CGH as the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
46
4
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 12 publications
9
46
4
1
Order By: Relevance
“…Furthermore, gene content was also evaluated using databases such as the NCBI Gene Database, GeneCards, and OMIM. CNVs were classified as described by Miller et al (2010) and were classified into 4 groups: I) causatives, when associated with known microdeletion/microduplication syndromes; II) probably causative, when the CNV was not previously associated with known microdeletion/microduplication syndromes, but contained genes known to cause a syndrome of a clear phenotype (Ahn et al, 2013) or because similar CNVs were already described in patients from other studies; III) noncausative (benign); IV) VOUS, variants of unknown clinical significance.…”
Section: Analysis and Cnv Classificationmentioning
confidence: 99%
“…Furthermore, gene content was also evaluated using databases such as the NCBI Gene Database, GeneCards, and OMIM. CNVs were classified as described by Miller et al (2010) and were classified into 4 groups: I) causatives, when associated with known microdeletion/microduplication syndromes; II) probably causative, when the CNV was not previously associated with known microdeletion/microduplication syndromes, but contained genes known to cause a syndrome of a clear phenotype (Ahn et al, 2013) or because similar CNVs were already described in patients from other studies; III) noncausative (benign); IV) VOUS, variants of unknown clinical significance.…”
Section: Analysis and Cnv Classificationmentioning
confidence: 99%
“…Taking a practical focus, Ahn et al 72 reported on a study at Guy's and St. Thomas' NHS Foundation Trust in London using oligonucleotide aCGH as a first-line diagnostic test in place of karyotyping for postnatal referrals (ranging from neonatal congenital anomalies to adult neurodisabilities). Two-thirds of the patients tested with aCGH (8794/13,412) had this as their first-line test.…”
mentioning
confidence: 99%
“…For cases with completed inheritance studies (about 50% of the patients with imbalances), one-fifth of the imbalances were de novo. With regard to the potential limitations of aCGH, Ahn et al 72 point out that, despite the increase in resolution and the higher diagnostic yield associated with aCGH testing, there may be concern that, without visualisation of chromosomes by traditional cytogenetic techniques, balanced rearrangement will not be detected. These rearrangements may disrupt gene function without causing any loss of coding material and hence may be important diagnostically.…”
mentioning
confidence: 99%
“…The resolution will depend on the specific platform used; the 5 oligonucleotide platform used at our centre has an 8x60K format, and a resolution across the 6 genome of approximately 120kb; this results in detection of imbalance in 25% of our patients 7 after exclusion of known benign CNV (Ahn et al 2013). However, approximately 40% of 8 these imbalances are small in size and of unknown clinical significance.…”
mentioning
confidence: 99%